2008 Australasian Telecommunication Networks and Applications Conference 2008
DOI: 10.1109/atnac.2008.4783348
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent Model to Control Preemption Rate of Instantaneous Request Calls in Networks with Book-Ahead Reservation

Abstract: Abstract--Resource sharing between Book-Ahead (BA) and Instantaneous Request (IR) reservation often results in high preemption rate of on-going IR calls. High IR call preemption rate causes interruption to service continuity which is considered as detrimental in a QoS-enabled network. A number of call admission control models have been proposed in literature to reduce the preemption rate of on-going IR calls. Many of these models use a tuning parameter to achieve certain level of preemption rate. This paper pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Once the model is trained it automatically estimate the tuning parameter value essential to achieve the desired level of preemption rate. The simulation result clearly identified that the model closely matche's with the target rate and reduce the preemption rate of on-going IR calls [5].…”
Section: Related Workmentioning
confidence: 64%
See 1 more Smart Citation
“…Once the model is trained it automatically estimate the tuning parameter value essential to achieve the desired level of preemption rate. The simulation result clearly identified that the model closely matche's with the target rate and reduce the preemption rate of on-going IR calls [5].…”
Section: Related Workmentioning
confidence: 64%
“…Training algorithms SCR &BR provide mean error 2.51% &1.88% respectively [5]. Link capacity optimization is created by on-line training with back propagation.…”
Section: Intelligent Model To Control Preemption Rate In Network Witmentioning
confidence: 99%
“…A paper inspired from developing various mathematical approaches to solving the call admission control problem is described for the usage of Markov decision process, fuzzy logic, neural networks and genetic algorithms was introduced Which was trained through certain learning process able maintain automatically dynamically resource shearing between previous allocated resources and new instantaneous call request to achieve the desired level of preemption rate for new call [11] [12]. In this research paper proposed a fuzzy neural approach for call admission control in heterogeneous network having different class traffic and load for upcoming based new generation cellular network.…”
Section: Related Workmentioning
confidence: 99%